A workflow for hydroacoustic source analyses based on a scale-resolving flow simulation of a hubless propeller. (1st October 2022) - Hieke, M.; Sultani, H.; Witte, M.; von Estorff, O.; Wurm, F.-H.
Abstract: The steady increasing noise level in the oceans caused by shipping traffic and the resulting disturbance of marine mammals enhances the need for environmentally sustainable quiet ship propulsion systems. Acoustic optimizations as well as alternative propulsion concepts are able to reduce the noise emissions of ships. In terms of alternative propeller concepts, hubless propellers are a particularly interesting object of research due to their modified blade geometry and compact design. This work builds on a workflow that allows to calculate and analyze the hydroacoustic pressure field of a marine propeller. The transient pressure and velocity fields from a stress blended eddy simulation (SBES) of the hubless propeller was used for the calculation of the resulting hydroacoustic field using the expansion about incompressible Flow (EIF) approach. The calculation of the acoustic field is performed in a second step after the calculation of the flow field, which avoids the problem of the large disparity of time and length scales between the hydrodynamic and the acoustic field quantities. In addition, coherent flow structures were filtered using the proper orthogonal decomposition (POD) method for specific analysis of the hubless propeller hydrodynamic and hydroacoustic. The acoustic source term ∂ p / ∂ t was furthermore calculated from the POD modes and time coefficients and used for the hydroacoustic analysis in order to identify dominant source regions of individual tonalities. Thus, this research aims to provide a workflow for hydroacoustic calculation and analysis as well as an approach for optimizations of marine propellers. Highlights: High resolved detached eddy simulation (DES-SBES) of the unsteady wake flow of a ducted hubless propeller Analyses of the hydroacoustic sound field based on expansion about incompressible flow (EIF) approach Experimental validation of the hydro dynamic and acoustic results Filtering of the periodic coherent flow structures using proper orthogonal decomposition (POD) analysis Calculation method and analysis of the acoustic source term based on single coherent flow structures.